Association of Systemic Inflammatory Factors with Progression to Advanced Age-related Macular Degeneration. (4th March 2022) - Wagner, Brandie D.; Patnaik, Jennifer L.; Palestine, Alan G.; Frazer-Abel, Ashley A.; Baldermann, Rebecca; Holers, V. Michael; Mathias, Marc T.; Mandava, Naresh; Lynch, Anne M.
ABSTRACT: Purpose: Age-related macular degeneration (AMD) is a leading cause of vision loss in the elderly. The role of systemic inflammation in AMD remains unclear specifically in patients with intermediate AMD (iAMD). We sought to determine whether systemic inflammation was associated with future iAMD progression. Methods: Combinations of 27 circulating inflammatory markers including complement factors, cytokines, chemokines, and high-sensitivity C-reactive protein (hsCRP) were evaluated in iAMD patients recruited into a Colorado AMD registry. Systemic inflammatory markers were combined using principal component analysis. Risk factors for AMD progression were evaluated using Cox regression models. Results: This study included 99 subjects with iAMD, 21 of which progressed to advanced AMD. Two principal components (PCs) were identified that contributed to the risk of progression to advanced AMD, after adjusting for age and bilateral reticular pseudodrusen. The strongest associated PC was explained largely by the pro-inflammatory cytokine TNFα and the anti-inflammatory IL1ra antagonist of IL1. The additional PC was largely explained by IL6, IL8, C3 and factor D in the positive direction and CRP, MCP1, factor B and factor I in the negative direction. Conclusion: When evaluated through multivariate analyses, combinations of biomarkers distinguished patients who did and did not progress to future advanced AMD. Increased risk could result from different combinations of analyte levels indicating a complex relationship rather than a simple increase in a few markers. This suggests that studying systemic inflammation in iAMD can provide insights into early pathologic events and potentially identify patients at highest risk for the development of severe AMD.